Patients With Suspected Severe Adverse Reactions to COVID-19 Vaccination Admitted to Intensive Care Unit: A Case Report - Battaglini, Denise; Ball, Lorenzo; Robba, Chiara; Maiani, Simona; Brunetti, Iole; Benedetti, Luana; Castellan, Lucio; Zona, Gianluigi; Pesce, Giampaola; Rocco, Patricia R. M.; Pelosi, Paolo (Frontiers in Medicine, 2022)
Background: Several cases of adverse reactions following vaccination for coronavirus disease 2019 (COVID-19) with adenoviral vector vaccines or mRNA-based vaccines have been reported to date. The underlying syndrome has been named “vaccine-induced immune thrombotic thrombocytopenia” (VITT) or “thrombosis with thrombocytopenia syndrome (TTS)” with different clinical manifestations. Methods: We report the clinical course of five patients who had severe adverse reactions to COVID-19 vaccines, either with VITT/TTS, abdominal or pulmonary thrombosis after adenoviral vaccines, or Stevens’ Johnson syndrome because of mRNA vaccination, all of whom required admission to the intensive care unit (ICU). Conclusions: All patients with severe or life-threatening suspected reaction to different types of COVID-19 vaccination required ICU admission. A prompt evaluation of early symptoms and individualized clinical management is needed to improve outcomes.